The Mediating Role of Satisfaction in the Relationship between Service Quality and Loyalty: Case Study in PT Asuransi XYZ Indonesia. - Roby Nurismartian; Prof. Ir. Hendra Michael Roy Sembel, MBA., Ph.D., CSA (International Journal of Business Studies, 2020)
The objective of this study is to analyze the relationship of service quality on agents’ satisfaction, service quality on agents’ loyalty, and satisfaction on loyalty when they used the insurance portal XYZNet as a digital tools provided by PT Asuransi XYZ Indonesia for their agents’ to increase market share in retail business in Indonesia. Where the portal was facing the challenge of the low number of usage. This study used a quantitative approach, involved 100 respondents which have minimum five times using this portal as samples. The analysis technique used in this study is Partial Least Square (PLS) Structural Equation Modeling (SEM), with the help of SmartPLS version 3.2.8 software. The results indicated that service quality positively influenced agents’ satisfaction, satisfaction also positively influenced agents’ loyalty. However service quality did not significantly influenced agents’ loyalty. The finding also indicated that satisfaction was a significant variable that mediated the relationship between service quality and loyalty. The study gives positive impact to the future researchers to do similar study. Furthermore, the finding could help PT Asuransi XYZ Indonesia and insurance company in general to improve their service quality.